Registration of OK05312, a High‐Yielding Hard Winter Wheat Donor of Cmc4 for Wheat Curl Mite Resistance. Issue 1 (3rd December 2015) - Carver, Brett F.; Smith, C. Michael; Chuang, Wen-Po; Hunger, Robert M.; Edwards, Jeffrey T.; Yan, Liuling; Brown-Guedira, Gina; Gill, Bikram S.; Bai, Guihua; Bowden, Robert L.
Abstract : Wheat streak mosaic (WSM) is a devastating disease in the High Plains region that is advancing eastward toward lower elevations. Its control is best achieved by combining known disease resistance genes with resistance to the insect vector. A hard red winter (HRW) wheat ( Triticum aestivum L.) germplasm line, OK05312 (Reg. No. GP‐995, PI 670019), was co‐developed by Oklahoma State University, Kansas State University, the Wheat Genetics Resource Center, and USDA‐ARS and released in 2014. It possesses gene Cmc4 and confers strong resistance to the wheat curl mite (WCM, Aceria tosichella Keifer). OK05312 is an F4 –derived line from the double cross TX93V5919/KS96WGRC40//OK94P549/KS96WGRC34 and is expected to provide an improved source of Cmc4 over KS96WGRC40. OK94P549 was the parent line from which HRW cultivar Endurance was selected. OK05312 was released for its high grain yield potential in a late‐maturing background with resistance to the with resistance to the wheat soil‐borne mosaic–wheat spindle streak mosaic complex and acceptable milling and baking quality. Hence, OK05312 provides wheat breeders an alternative source of WCM resistance and a critical component to mitigate yield losses to WSM and other WCM‐transmitted viruses.